Application of dumping and transfer methods to study in vitro dissolution behavior and precipitate of the poor water soluble weak base drug: Carvedilol case - Ahmed Ali Hashim Al - Ameri; Masar Basim Mohsin Mohamed (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
This work intended to evaluate the dissolution of poor water soluble weakly basic drug like carvedilol (Carv) via two methods used to study and assess the effect of pH changes from the stomach to the small intestine on the drug dissolution and precipitation (ppt): dumping and transfer. Three approaches were used to increase solubility and decrease the precipitation of carvedilol; first, the acid modification principle was by incorporating Carv with fumaric acids (FA) to keep the drug at a low pH in the intestine. The second approach was solvent evaporation, which converted the drug from a low soluble crystalline form to a highly soluble amorphous form, and the last approach was forming a slow-release floating dosage form. The prepared samples were investigated by FESEM and FTIR. There is a slight shift in the peaks related to the hydroxyl group in approaches (acid modification and solvent evaporation) compared to the peak’s position in the Carv spectrograms, and the FESEM shows a decrease in particle sizes of prepared samples. The Carv prepared samples in vitro dissolution of dumping, and the transfer showed different in vitro dissolution profiles with enhanced dissolution profiles and lower ppt amount. The amorphization technique’s ppt was highly decreased in both dissolution dumping and transfer methods compared to the in vitro dissolution of the control of Carv.